Profil Kemampuan Berpikir Kritis Siswa dalam Menyelesaikan Soal Fungsi Komposisi dengan Model Pembelajaran Kolaboratif - Bela, Maria Editha; Coo Bule, Modesta Venidora; Wewe, Melkior; Tali Wangge, Maria Carmelita (Supermat : Jurnal Pendidikan Matematika, 2024)
ABSTRACT The aim of this research is to find out how critical mathematical thinking abilities of students at SMA Negeri 1 Boawae are in solving composition function problems using a collaborative learning model. This type of research is descriptive research using a qualitative approach. This research can be used as a reference for educators to identify the profile of students' mathematical critical thinking abilities. Critical thinking is a type of higher level thinking. Learning mathematics in the era of globalization usually uses critical thinking in solving problems, because mathematics is seen as the most difficult subject. Data collection is carried out by observation, documentation and tests. The subjects of this research were 3 students in class XI F3 of SMA Negeri 1 Boawae, one high achieving student, one medium high achieving student, and one low achieving student. Gifted students can meet all critical thinking standards and participate actively in teaching and learning activities. Students who achieve moderately only fulfill the focus on the first and second indicators, inference, situation, clarity and description on the second indicator, and can join in collaborative learning. Meanwhile, students with low abilities are not actively involved in collaborative learning and only achieve focus on the first and second indicators. The results of the research show that students' critical mathematical thinking skills in composition function material are relatively low.